Strategi Peningkatan Volume Tinja yang Masuk ke Instalasi Pengolahan Lumpur Tinja Menggunakan Metode Regresi Logistik dan Analytical Hierarchy Process Multilevel - Fega Belindasari Nasution; Irwan Bagyo Santoso (Jurnal Serambi Engineering, 2024)
This study assesses the technical, social, and economic aspects of IPLT with the objective of increasing the volume of fecal matter entering IPLT in Lamongan Regency. The analysis of the existing condition of IPLT, the interviews with stakeholders, and the logistic regression with NCSS identified the main factors influencing the low stool volume. The results demonstrated that land height (Coefficient 3.5318, Odds Ratio 34.18547) and income (Coefficient 0.03151, Odds Ratio 1.03201) had a statistically significant impact on the frequency of fecal suction. The strategic priorities identified through AHP are IPLT capacity building, community education, and effective implementation of retribution. The program is supported by the participation of the community (65.1%), the government (27.9%), and IPLT members (7%) with a sustainable circular economy approach.